Evaluation of the degradation of two bioabsorbable interference screws: an in-vivo study in sheep - Scorsato, Paulo Sérgio; Rahal, Sheila Canevese [UNESP]; Cestari, Tania Mary; Mamprim, Maria Jaqueline [UNESP]; Doiche, Danuta Pulz [UNESP]; Teixeira, Daniel de Bortoli; Siqueira, Rafael Cerântola [UNESP]; Felix, Marcílio (FapUNIFESP (SciELO), 2022)
Purpose: To evaluate in-vivo degradation of two bioabsorbable interference screws. Methods: Twenty-two crossbred Santa Inês ewes were used. A poly-DL-lactide (PDLLA) screw (70%/30%) was inserted in the right pelvic limb, and a PDLLA screw (70%) + β-tri-calcium phosphate (β-TCP) (30%) in the left pelvic limb. Animals were euthanized at one, four, seven and a half and 18 months after surgery. Plain radiography, computed tomography (CT), microCT, and histological analysis were accomplished. Results: PDLLA screw was hypodense at all evaluation moments, but with progressive density increase along the central axis, whereas PDLLA/β-TCP was initially hyperdense and progressively lost this characteristic. No adverse reactions were observed on histological evaluation. Conclusions: The inclusion of β-TCP favors screw degradation since the PDLLA/β-TCP screws evidenced a more intense degradation process than the PDLLA screws at the last evaluation. PDLLA screws showed higher bone production, evident around the screw thread, inside the lateral perforations, and in the central canal, whereas the PDLLA/β-TCP screws presented less bone tissue at the implantation site.
Keywords: Absorbable Implants; Bone Screws; Polylactic Acid-Polyglycolic Acid Copolymer; Sheep